(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The financial market plays a pivotal role in the overall economy, functioning as a platform for the exchange of funds, securities, and various financial instruments. This article delves into the economic essence of the financial market, highlighting its significant aspects and the key components that drive its operation.